Konsep Pendidikan Anak dalam Perspektif Ajaran Agama Islam - Asep Solikin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
The basic component that makes up the human person who is recognized by Islam is the body, soul, and mind. Therefore, the education of children, in general, can be divided into three main groups. If it fails to determine the orientation of education, obviously also resulted in failure in achieving business results performed. The three components are the united of whole and round. Therefore, concern for these components must be balanced, should not be biased. In another word, that the orientation of the education of children patterned into three main objectives, namely: the purpose of education, physical, spiritual educational purposes, and educational purposes aqliah.